Bacterial Culture of Tear Duct Infections Secondary to Congenital Nasolacrimal Duct Obstructions - Weiming Yang; Li Shen; Anken Wang; Meiyan Li; Chenhao Yang (Journal of Ophthalmology)
Purpose. To investigate the microbial profile of congenital nasolacrimal duct obstruction (CNLDO) in Chinese children. Methods. We retrospectively reviewed the medical records of 330 consecutive children (330 eyes) who were diagnosed with tear duct infections secondary to CNLDO and were admitted to the Children’s Hospital of Fudan University from January 2013 to January 2020. Bacterial cultures were grown from tear duct samples of each patient. Samples from conjunctival secretions were cultivated on blood or chocolate agar. Clinically significant bacterial growth was reported. Results. Of the 330 eyes considered, 62.7% (207/330) were associated with positive bacterial cultures. A total of 223 isolates were detected from 207 culture-positive eyes. Among the 223 isolates, 52.0% (116/223) were Gram-positive bacteria and 47.1% (105/223) were Gram-negative bacteria. The most prevalent Gram-positive bacteria were Streptococcus viridans (67 isolates, 30%), followed by Staphylococcus aureus (36 isolates, 16.1%) and Streptococcus pneumoniae (5 isolates, 2.2%). The most prevalent Gram-negative bacteria were Neisseria (nonpathogenic) (25 isolates, 11.2%), followed by Escherichia coli (16 isolates, 7.2%) and Haemophilus influenzae (16 eyes, 7.2%). Antibiotic susceptibility test results suggested that both Gram-positive and Gram-negative bacteria were highly sensitive to most of the tested antibiotics. Conclusions. S. viridans and S. aureus are the most prevalent bacteria in tear duct infections secondary to CNLDO. Broad-spectrum antibacterial eye drops are suggested as empirical antibiotic treatments.